Isolation of Triterpenoid Glycoside from Bark of Terminalia arjuna using Chromatographic Technique and Investigation of Pharmacological Behavior upon Muscle Tissues - Tanushree Patnaik; R. K. Dey; Panchanan Gouda (E-Journal of Chemistry)
This study reports the isolation and characterization of a new triterpenoid glycoside extracted from the bark of Terminalia arjuna. The isolation of the organic compounds was done using simple chromatographic technique. Compound characterization using various spectroscopic technique identify the final isolated compound as Olean-3β,22β-diol-12-en-28β-D-glucopyranoside-oic acid. The method of isolation is simple, cost effective and efficient. The preliminary bioactivity of the compound was also evaluated.